Outcomes of direct pulp capping: interrogating an insurance database. (7th November 2015) - Raedel, M.; Hartmann, A.; Bohm, S.; Konstantinidis, I.; Priess, H. W.; Walter, M. H.
Abstract: Aim: To evaluate the effectiveness of direct pulp capping under general practice conditions. It was hypothesized that direct pulp capping is an effective procedure in the majority of cases and prevents the need for root canal treatment or extraction. Methodology: Claims data were collected from the digital database of a major German national health insurance company. Only patients who had been insurance members for the entire 3 year period 2010 to 2012 were eligible. Kaplan–Meier survival analyses were conducted for all teeth with direct pulp capping. Success was defined as not undergoing root canal treatment. Survival was defined as not undergoing extraction. Differences between survival functions were tested with the log rank test. Results: A total of 148 312 teeth were included. The overall success rate was 71.6% at 3 years. The overall survival rate was 95.9% at 3 years. The success rates for single‐rooted teeth (71.8%) and multirooted teeth (71.5%) were similar although significantly different ( P < 0.001). Best 3‐year success rates were found at low (79.7%; <18 years.) and very high age (81.8%; >85 years.). Conclusions: After direct pulp capping, more than two‐thirds of the affected teeth did not undergo root canal treatment within 3 years. Although this study has the typical limits of a claims data analysis, it can be concluded that direct pulp capping is an effective intervention to avoid root canal treatment and extraction in a general practice setting.